2018
DOI: 10.1002/bkcs.11627
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of (S,S)‐Reboxetine

Abstract: Advents of asymmetric reactions employing asymmetric reagents or catalysts are regarded as a paradigm shift in the field of stereoselective synthesis. In this paradigm, choices of the appropriate asymmetric reagents/catalysts control the configurations of newly created stereocenters (reagent-control). 1 This is in contrast to the traditional substrate-control, in which a pre-existing stereocenter in the starting material induces the configurations of newly created stereocenters in the product. 2 The archetype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…As a classic 3D QSAR method, comparative molecular field analysis (CoMFA) has been widely applied in molecular modeling . To design hypertensive agents, CoMFA has been employed to build a 3D QSAR model for the ACE inhibitors . However, it has been reported that the CoMFA method has several limitations.…”
Section: Introductionmentioning
confidence: 99%
“…As a classic 3D QSAR method, comparative molecular field analysis (CoMFA) has been widely applied in molecular modeling . To design hypertensive agents, CoMFA has been employed to build a 3D QSAR model for the ACE inhibitors . However, it has been reported that the CoMFA method has several limitations.…”
Section: Introductionmentioning
confidence: 99%
“…11,10c Interestingly, CuCl could also slightly improve the reaction (entry 10, see also the ESI †). Other bases or solvents were also evaluated, but no increase in the yield of the desired product was observed (entries [11][12][13][14]. Other Rh catalysts were then tested (entries 15-18), and only [Rh(cod)OH] 2 could lead to rather high yield of the product (entry 17).…”
mentioning
confidence: 99%